Vertical integration, disintegration and ability to export - Giampaolo Rossini; Laura Vici (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2007)
Recent literature on trade has emphasized the role of firms' heterogeneities in export performance and trade specialization of countries (Melitz, 2003; Melitz and Ottaviano, 2005). Exporting seems to be a strategy available only to most efficient and productive firms even in a framework with transport costs and no reciprocal dumping. We do not know much about the internal organization of these smarter companies which are exporting part of their production. However, from related theoretical (Helpman, 2006) and empirical (Rossini and Ricciardi, 2005) literature we know that more efficient firms tend to be more vertically integrated than the average population on both a domestic and a crossborder basis. Themain purpose of this paper is to link the two streams of literature on firms heterogeneities and export, on one side, and vertical integration and export, on the other side. Then, we try to answer the question: is the exporting activity going to affect the degree of vertical integration making exporting firms more vertically integrated than non exporting firms? And, if so, why? We investigate these matters at a theoretical tier and through a set of econometric tests on firm level data for 25 EU countries. At the theoretical level we consider a model with two countries each possessing one or two firms: one in case of vertical integration and two in case of vertical disintegration. We compare large and small vertically disintegrated or integrated firms in an environment with transport costs and home bias. Larger firms tend to be more vertically integrated and to engage in export activity. The theoretical conclusions are consistent with the empirical analysis which says that for larger firms exporting activity tends to boost the degree of vertical integration. This provides some link between the two literatures, the first maintaining that only more productive firms export and the second stating that more productive firms are more vertically integrated. The emphasized link dictates that the more enterprises export the more vertically integrated they are. Why? It is mostly a matter of size and R&D commitment which enhances productivity.
Keywords: 330